1997
DOI: 10.4319/lo.1997.42.1.0029
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic analysis of riverine bacterioplankton production

Abstract: Bacterial production is the entry point for detrital macronutrients into aquatic food webs. Many factors affect productivity, but the heterogeneity of detrital substrates and the diversity of microbial communities confound simple relationships between carbon supply and growth. WC tried to link the two by analyzing extracellular enzyme activities. Water samples were collected from three rivers and assayed for bacterial productivity and the activities of eight enzymes. Production varied among systems, peaking at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 49 publications
6
129
4
Order By: Relevance
“…Jacobsen & Rai (1991 reported that LAP activity increased with the degree of lake eutrophication. Kroer et al (1994) found that specific LAP activities were similar among marine, estuarine and riverine bacterioplankton despite wide differences in the concentration of inorganic N. Similar observations were made by Sinsabaugh et al (1997) in a comparison of 3 large rivers. Muller-Niklas et al (1994) reported that cell-specific activities of LAP and other enzymes were similar for bacteria associated with marine snow and for those suspended in the surrounding seawater.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Jacobsen & Rai (1991 reported that LAP activity increased with the degree of lake eutrophication. Kroer et al (1994) found that specific LAP activities were similar among marine, estuarine and riverine bacterioplankton despite wide differences in the concentration of inorganic N. Similar observations were made by Sinsabaugh et al (1997) in a comparison of 3 large rivers. Muller-Niklas et al (1994) reported that cell-specific activities of LAP and other enzymes were similar for bacteria associated with marine snow and for those suspended in the surrounding seawater.…”
Section: Introductionsupporting
confidence: 66%
“…Several studies have correlated peptidase activities with substrate availability, substrate uptake and bacterial productivity (e.g. Hoppe et al 1988, Miinster 1991, Muller-Niklas et al 1994, Sinsabaugh et al 1997, Foreman et al 1998). Jacobsen & Rai (1991 reported that LAP activity increased with the degree of lake eutrophication.…”
Section: Introductionmentioning
confidence: 99%
“…Assays associated with the large bottle amendments were conducted at ambient laboratory temperature (ϳ20ЊC). Sodium bicarbonate (4 mmol L Ϫ1 ) was substituted for whole water in substrate controls, whereas quench standards were prepared using whole water and 1 mol L Ϫ1 of 4-methylumbelliferone (Sinsabaugh et al 1997). Enzyme activities were calculated using a reference standard containing 1 mol L Ϫ1 of 4-methylumbelliferone.…”
Section: Methodsmentioning
confidence: 99%
“…phenol oxidase) represents an index of the quality of the dissolved organic C pool (LCI; Sinsabaugh and Shah 2011). All EEA assays used the microplate protocols originally developed by Sinsabaugh and colleagues (Sinsabaugh et al 1997;Sinsabaugh and Foreman 2001) and modified according to Hill et al (2010). Each microplate array included quadruplicate assays for each enzyme and each reference standard.…”
Section: Extracellular Enzymes Activities (Eea)mentioning
confidence: 99%